Indonesian Ongole Cattle Rural Breeders Income Based on Marketing Channel Analysis - Hariadi Darmawan; Ariani Trisna Murti; Marianus Rawa Tamba; Erlangga Esa Buana (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2021)
Beef cattle are essential among Indonesian farmers as supporting assets and livelihood through cattle breeding especially for rural breeders with the most preferred breed is Indonesian Ongole cattle known as PO cattle. It is essential to analyze and determine the PO cattle rural breeders' income based on the marketing channel analysis. The study aimed to determine the marketing channel's efficiency and the PO cattle rural breeders' income. This study site was Bojonegoro regency, stipulated as The National Agricultural Site of beef cattle commodity in the East Java Province. Ninety-three respondents were chosen based on a stratified random sampling of marketing channel stakeholders. This is a quantitative descriptive study with a cross-sectional survey method. Marketing channel analysis and marketing efficiency analysis compare with the PO cattle price level using descriptive statistical analysis. The result shows six marketing channels involve in delivering PO cattle to the last consumer as beef meat. It can be concluded that the fourth marketing channel is the most efficient marketing channel that gives the highest income for PO cattle rural breeders.Keywords: Marketing efficiency, National Agricultural Site, PO cattle, price, rural breeders